Biosynthesis of selenium nanoparticles as a potential therapeutic agent in breast cancer: G2/M arrest and apoptosis induction - Basant A. Ali; Rasha Mosa Allam; Mohamed S. Hasanin; Amany A. Hassabo (Toxicology Reports)
The drawbacks and adverse reactions of conventional breast cancer (BC) medications have prompted researchers to seek novel therapeutic approaches. This study aimed to study the impact of biosynthesized selenium nanoparticles by yeast on breast cancer (MCF-7) cells and to find potential underlying mechanisms. Therefore, marine yeast isolates were screened for their ability to biosynthesis selenium nanoparticles (SeNPs). The most potent isolate was identified as Candida pseudojiufengensis based on 18 S rRNA gene sequencing. Incubation of cell-free extract with 0.8 mM of SeO2 for 48 h at 40°C in pH of 7.0 were optimal conditions for the biosynthesis of SeNPs. The biosynthesized SeNPs were characterized by UV–Vis spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), and dynamic light scattering (DLS) measurements including average particle size distribution and average zeta potential. The results showed that the biosynthesized SeNPs displayed a maximum absorbance peak in the UV-Vis spectrum at 560 nm due to surface plasmon resonance. TEM image elevated spherical shape particles with an average size of 12 nm. SRB assay, flow cytometry, and other biochemical methods were employed to assess SeNPs anti-proliferative effects on MCF-7 cells. SeNPs showed superior anticancer efficacy against MCF-7 cells compared to colon (HCT-116) and liver (HepG2) cancer cells, as evidenced by lower IC50 values (19.59 µg/ml) against 36.36 µg/ml and 27.81 ±1.4 µg/ml, respectively. However, SeNPs demonstrated no cytotoxic effects against HSF cells. Moreover, treatment with SeNPs induces G2/M arrest along with triggering apoptosis in MCF-7 cells. Furthermore, MCF-7 cells treated with SeNPs showed increased oxidative stress, as indicated by observable rises in LPO and 8-OHDG, accompanied by considerable exhaustion in antioxidant enzyme activity. These findings demonstrated that Se nanoparticles synthesized from yeast have therapeutic promise in BC treatment.